The Versilia’s Outpatient Consultation Centre for Occupational Medicine - Bramanti, Lucia; Mariani, Maurizio; Verola, Paola; Bertagna, Federica; Ceragioli, Valeria (La Medicina del Lavoro, 2018)
For many years now, an outpatient consultation clinic dedicated to the diagnosis of work-related illnesses has been operating at the headquarters of the Department of Prevention, Hygiene and Safety in Work Places (UF PISLL) of the USL (local health division) for Northwest Tuscany in the Versilia territory, in particular for musculoskeletal illnesses. Outpatient activities permit for continuous observation of work related activities potentially posing a risk to health, to intercept disturbances or possible early/reversible pathologies, and to provide guidance for risk management at the workplace. In the case of musculoskeletal and respiratory diseases, the visit is followed by a direct execution of specific instrumental examinations for a targeted diagnosis. Ambulatory users are homogeneous groups of workers, but also individual workers (or former workers) sent by occupational physiciants of the Companies, general medical practitioners or specialist doctors. The annual turnout exceeds 300 people on average, and has so far allowed not only the emergence of work-related illnesses but also intercepting work activities with biomechanical overload or other health risks otherwise misdiagnosed.The possibility of directly carrying out some instrumental in depth studies has stimulated research for pathologies that are still reversible, which can be improved with interventions on the individual and/or the workplace, also for the purpose of reintegration into the workplace. The activity has also ensured the awareness of many other operators in the field of work-related illnesses that, in the Versilia territory, are very numerous in terms of complaints and INAIL (National Institute for Insurance against Accidents at Work) acknowledgments, even with respect to the rest of Tuscany.